2021
DOI: 10.1097/aln.0000000000003726
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Triggering Dyssynchrony 24 h after Initiation of Mechanical Ventilation

Abstract: Background Reverse triggering is a delayed asynchronous contraction of the diaphragm triggered by passive insufflation by the ventilator in sedated mechanically ventilated patients. The incidence of reverse triggering is unknown. This study aimed at determining the incidence of reverse triggering in critically ill patients under controlled ventilation. Methods In this ancillary study, patients were continuously monitored with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Second, even when all mechanical breaths are initiated by time (i.e., controlled), a patient's breathing effort might still occur in the form of reverse triggering efforts in which patient's breathing efforts are "entrained" by the passive insufflations [25], a phenomenon which is very frequent in the transition from fully controlled to assisted mechanical ventilation [26] (see Fig. 4).…”
Section: Technical Aspects and Modes Of Mechanical Ventilationmentioning
confidence: 99%
“…Second, even when all mechanical breaths are initiated by time (i.e., controlled), a patient's breathing effort might still occur in the form of reverse triggering efforts in which patient's breathing efforts are "entrained" by the passive insufflations [25], a phenomenon which is very frequent in the transition from fully controlled to assisted mechanical ventilation [26] (see Fig. 4).…”
Section: Technical Aspects and Modes Of Mechanical Ventilationmentioning
confidence: 99%
“…We supposed that the proportional relationship between diaphragm contraction force and ventilator energy played the key role in the occurrence of RT, which was in line with the mechanisms of the entrainment. Recently Mellado Artigas et al (2021) found that the incidence of RT was higher in patients who had more patient-triggered breaths or were more likely to be extubated. Their retrospective results also support our assumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent literature has been unable to show a significant correlation between sedative dosing and incidence of reverse triggering ( Rodriguez et al, 2020a ). Other reports suggest that the occurrence of reverse triggering may represent the transition between deep sedation and recovery of the patient’s respiratory drive ( Mellado Artigas et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%